Coalesced‐Droplets Transport to Apexes of Magnetic‐Flexible Cone‐Spine Array. Issue 23 (4th November 2016) - Wang, Lei; Zhang, Miaoxin; Gao, Chunlei; Zheng, Yongmei
Abstract : Coalesced‐droplets can be driven to transport to apexes of magnetic‐flexible cone spine from the bottom due to formation of wettability gradient on superhydrophobic spine with nanohairs.